NILAI-NILAI DALAM RITUAL BASARAH - Wentin MPdH (Fakultas Dharma Duta, 2018)
Devotion to God is a necessity for every religious person.Hindus explain the teachings of Bhakti in the Bhagavata Purana known as Navavida Bhakti.The actualization of devotional service in Hinduism has diversity but is essentially the same. Therefore, there are differences in the practice of devotional service for Hindus in various regions.This happened to Hinduism in Central Kalimantan (Hindu Kaharingan).This paper describes four important things related to the implementation of the Basarah for Hindu Kaharingan in Central Kalimantan. The four things are basarah philosophy, the procedure of basarah, sajen basarah, and the values ​ ​ contained in the implementation of basarah.